Influence winter swimming on post-exercise regeneration and quality of life of people practicing recreational sports - Zając, Kacper; Kupczak, Agata; Dolińska, Anna; Wilczek, Mateusz; Górka, Dariusz; Białoń, Natalia; Górka, Mikołaj (Journal of Education, Health and Sport, 2023)
Entry Swimming is a stress factor for the body, depending on the level of adaptation to this stimulus, there may be different reactions of the body. Therefore, the contraindications and risks of immersion in cold water, such as drowning or hypothermia, should be taken into account. The study was aimed at assessing the impact of cold baths on well-being and post-exercise regeneration. Materials and methods The study involved 244 people who regularly practice recreational sports and swim. Conclusions Swimming has a positive effect on well-being and post-workout regeneration. It is important to conduct more research to obtain the data needed to determine the long and short term effects of swimming in the context of recreational activities.